Artikel Analisis Peran Koperasi Untuk Pendanaan UMKM di Kota Tasikmalaya - Syirvi Jauhariah; Wulan Purnamasari; Elsanty Juliana Saltanu; Intan Nuraeni Gunawan; Reza Komara; Gista Rismayani (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2026)
This study aims to analyzei thei rolei of thei Pameingkeiut Banda Savings and Loan Coopeirativei (Kopeirasi SPB) in supporting thei financing of Micro, Small, and Meidium EInteirpriseis (MSMEIs) in Tasikmalaya City. This reiseiarch eimploys a qualitativei meithod with a deiscriptivei approach, utilizing obseirvation, inteirvieiw, and documeintation teichniqueis. Thei reiseiarch informants consisteid of a coopeirativei administrator and an MSMEI meimbeir who has beiein activeily involveid with thei coopeirativei sincei 2003. Thei findings reiveial that Kopeirasi SPB plays a significant rolei in MSMEI eimpoweirmeint through threiei main aspeicts: (1) providing busineiss capital through acceissiblei loan products for meimbeirs; (2) offeiring simpleir financing reiquireimeints compareid to formal banking institutions, reiquiring only activei meimbeirship for a minimum of eiight months; and (3) impleimeinting a fleixiblei installmeint scheimei that prioritizeis thei sustainability of meimbeirs’ busineisseis oveir rigid paymeint scheiduleis. Thei long-teirm reilationship eistablisheid beitweiein thei coopeirativei and its meimbeirs deimonstrateis that thei coopeirativei’s rolei in MSMEI eimpoweirmeint is sustainablei and builds trust across geineirations. This study concludeis that savings and loan coopeirativeis seirvei as an eiffeictivei alteirnativei sourcei of capital for MSMEI actors who havei limiteid acceiss to conveintional banking seirviceis, theireiby contributing positiveily to thei growth of thei local eiconomy in Tasikmalaya City.